Bioactivity Screening of Erechtites valerianifolia (Link Ex Wolf.) Less. Extracts as Antiplasmodium, Antibacterial, Antifungal and Cytotoxic Agents - Puspaningtyas, AR; Riyanto, S; Solikhah, EN; Astuti, P (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Indonesia’s rich natural resources have encouraged many researchers to explore their potential for finding treatment of endemic diseases and malignancy. One of these resources is Erechtites valerianifolia (Link Ex Wolf.) Less. Ex DC or "Jonggolan" (Indonesian name), a member of the family Asteraceae was collected from Meru Betiri Forest. Empirical evidence reveals the use of this plant to treat fever, diarrhea, tonsillitis, wounds, and eczema. A study in 2015 reported that the family Asteraceae passed the test of antioxidant and antibacterial activity. Yet, scientific information about E. valerianifolia has not been optimally explored, and studies of this plant are even very limited. Considering the background, this study was aimed to conduct bioactivity screenings of E. valerianifolia extracts as antiplasmodial, antibacterial, antifungal and was anticancer/cytotoxic agents. Extract was obtained through percolation method using hexane, dichloromethane, ethyl acetate, and methanol as the solvents. Gram positive bacteria (Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus and Bacillus cereus) and gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa) were used as the antibacterial testing microorganisms. Candida albicans was the antifungal testing microorganism. The results showed that extracts, at a concentration of maximum 1000 ppm, were less active than the positive-control amoxicillin for antibacterial activities and ketoconazole for antifungal agents. Inhibition zones of E. valerianifolia extracts were invisible when compared to the positive controls. The screening of antiplasmodial (P. falciparum FCR3) activity indicated that IC50 of ethyl acetate extract was 117.122 μg/ml and was considered the best among other extracts. The cytotoxicity study on MCF 7, WiDr and Hela cell lines showed that the four extracts tested had good cytotoxicity with IC50 < 30 μg/ml. Dhaka Univ. J. Pharm. Sci. 17(1): 1-8, 2018 (June)